E-205 In vitro evaluation of full-length, mr-safe interventional passive catheter markers at 3T. (23rd July 2022) - Kilbride, B; Jordan, C; Ahn, S; Mueller, K; Chu, A; Barry, D; Moore, T; Martin, A; Wilson, M; Hetts, S
Abstract : Introduction: MRI-guided intervention provides valuable functional information such as perfusion and diffusion that standard fluoroscopic guidance lacks. Recent studies have demonstrated utility in stroke treatment for multimodality X-ray and MR imaging suites. Yet, clinical adoption of MRI-guided intervention has lagged, and an absence of appropriate tooling could be a contributing factor. Prior work described a polymeric catheter featuring radiopaque markers doped with iron oxide nanoparticles (IONPs) as low-profile, MRI-visible passive markers. Here, we further investigate susceptibility artifacts in vitro at 0° and 90° with respect to B0 . Marker separation was evaluated to identify a potential format for full-length visibility at 3.0T. Methods: Polymeric, 6.6 Fr guide catheter segments were built in a fabrication facility (Penumbra, Inc., Alameda, CA). Epoxy-based radiopaque ink was mixed with 9.1 wt% (w/w) iron(III) oxide (Fe2 O3 ) nanoparticles of 20–40 nm diameter. Four circumferential marker bands ranging from 5 to 20 mm apart were applied in series starting 1 cm from the distal tip and cured at 20°C. 15-cm segments submerged in copper sulfate solution (CuSO4, 1–2 g/L) were oriented parallel (0°) and orthogonal (90°) with respect to B0 . At 0°, images were acquired in coronal/sagittal slice orientations on a 3.0T MRI scanner (MAGNETOM Skyra, Siemens Healthcare, Erlangen, Germany). At 90°, images were acquired in coronal/axial orientations to match image acquisition of 0°. Phase encoding direction was maintained parallel to the catheter major axes. T2-weighted turbo spin echo (TSE) and gradient echo (GRE) sequences were collected. Maximum artifact widths were evaluated per ASTM F2119–07, using ImageJ (http://imagej.nih.gov/ij). Results: Susceptibility artifacts induced by the IONP-doped markers are shown ( FIG. 1 ). 90° orientation produced worst-case artifacts in all sequences except the axial TSE. Furthermore, some artifacts could not be discerned at 90°. 20-mm separation yielded distinct artifacts without overlapping. Conclusion: Although worst-case artifacts were observed at 90°, they remained acceptable for use in guide catheters. Additionally, 20-mm marker separation could provide distinct artifacts down the length of a catheter during MRI-guided interventions, despite anatomic tortuosity. The phantom used in this study was shallow, which limited the ability to distinguish between real artifacts and those arising from the solution-air interface. Hence, accuracy of the degree of increased artifact may warrant further investigation. This study simulated worst-case orientations in vitro ; more data should be collected in vivo using real-time sequences to best evaluate artifacts during clinical use. Disclosures: B. Kilbride: None. C. Jordan: None. S. Ahn: 5; C; Siemens Medical Solutions USA Inc. K. Mueller: 5; C; Siemens Medical Solutions USA Inc. A. Chu: 5; C; Penumbra Inc. D. Barry: 5; C; Penumbra Inc.. T. Moore: None. A. Martin: None. M. Wilson: None. S. Hetts: None.